2020
DOI: 10.1111/inm.12773
|View full text |Cite
|
Sign up to set email alerts
|

Repeat presentations to the emergency department for non‐fatal suicidal behaviour: Perceptions of patients

Abstract: Presentations to emergency departments (EDs) for non‐fatal suicidal behaviour (NFSB) are increasing in Australia and overseas. Our understanding of the factors contributing to this trend remains unclear. In this qualitative phenomenological study, we explored patient perceptions of their ED experience and the interventions provided. The study group comprised 10 adults who had had 3 or more presentations to the ED in a 12‐week period for NFSB. Individual interviews were conducted in person with participants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…A 2013 study found that engaging with the help seeker as an individual deserving respect rather than simply treating the suicidal crisis facilitated help seekers’ positive self-evaluations and reducing feelings of hopelessness [ 26 ], and small acts of kindness in the ED can encourage help seekers to feel as though they are being considered more than just their presentation [ 27 ]. However, staff in EDs are under incredible pressure to provide high quality care with little resources [ 6 ], and as such, many staff focus on providing “treatment” for the condition rather than care for the individual in order to meet the demands of the busy ED setting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A 2013 study found that engaging with the help seeker as an individual deserving respect rather than simply treating the suicidal crisis facilitated help seekers’ positive self-evaluations and reducing feelings of hopelessness [ 26 ], and small acts of kindness in the ED can encourage help seekers to feel as though they are being considered more than just their presentation [ 27 ]. However, staff in EDs are under incredible pressure to provide high quality care with little resources [ 6 ], and as such, many staff focus on providing “treatment” for the condition rather than care for the individual in order to meet the demands of the busy ED setting.…”
Section: Discussionmentioning
confidence: 99%
“…The ED can be a challenging environment for help seekers as a place to seek care. Help seekers have indicated that the chaotic and fast-paced environment of the ED, combined with long waiting times, is detrimental to their vulnerable state of mind [6,7]. Negative staff attitudes, such as low empathy, and a focus on physical injury have resulted in help seekers reporting negative ED experiences [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations